Diversity of microcystins and non-microcystin-producing Microcystics population in the Dau Tieng reservoir, Vietnam - Luu, Pham Thanh (Academia Journal of Biology, 2018)
In this study, a 16S rDNA clone library was used to evaluate the diversity of potential microcystin producing cyanobacteria and polymerase chain reaction (PCR) was used to analyze the diversity of this population based on the presence of the mcyD gene in samples collected during a bloom season. The results revealed that Microcystis genera from the Dau Tieng reservoir (DTR) contained several genotypes. The isolated Microcystis strains from the DTR were found to consist both toxic and non-toxic species within species and population. In total 35 strains acounted for 58% were found to produce a mixture of microcystins (MCs). All samples of cyanobacterial blooms in the DTR contained high amount of MCs which could pose health risk to aquatic systems and local people.